ANALISIS PEMASARAN TANAMAN HIAS PUCUK MERAH (OLEINA SYZYGIUM) PADA USAHA KEMBANG ASRI DI KOTA PALU - Feni Srawati; Abdul Muis (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
This study aimedto determinemarketing channels, marketing margins, part of the price received by producers,and marketing efficiency of ornamental red bud plants at Kembang Sari business. There were three channels found for marketing of the ornamental red bud (Oleina Syzygium) plants. The marketing marginsat the first channel for small, medium and large size of the flowers were IDR 20,000, IDR 20,000, and IDR 30,000, respectively, whereas for the second channel the margins were IDR 10,000, IDR 10,000, and IDR 20,000, respectively. The third channel had no margin due to none of marketing agencies involved.  The part of price generated by the producers for the three sizes of the plants at the first channel were 60%, 71.4% and 76.9%, respectively and at the second channel were 75%, 83.3% and 83.3%, respectively, whereas at the third channel, it was 100% for all sizes of the plants.  The marketing efficiencies for the three marketing channels were 16.19%, 24.60% and 19.00%, respectively. Keywords: Marketing channel, and Ornamental plants.